2021
DOI: 10.1108/ejim-01-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience approach for management and entrepreneurship: a bibliometric analysis

Abstract: PurposeThis study focuses on the role of individuals in the innovation management process, by concentrating on leaders and associated behaviors. Specifically, Entrepreneurial Leadership (EL) represent one of the most important fields of innovation management that has become increasingly multifaceted and interdisciplinary with its evolution. Thus, the purpose of this study is to examine a newly emerging research trend with a new lens that is “neuroscience”.Design/methodology/approachThis paper finds an evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 150 publications
(272 reference statements)
0
14
0
1
Order By: Relevance
“…Similarly, describing the theoretical and practical contribution of neuroentrepreneurship is difficult. Studies have investigated the practical implications of neuroscience in the field of management and entrepreneurship through coupling and co-citation analyses (Cucino et al, 2021), but these researchers have not clearly described the respective differences. In this study, we observed that neuroscience and entrepreneurship have a clear relationship; thus, discussing the common methodologies and trends underlying neuroentrepreneurship research is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, describing the theoretical and practical contribution of neuroentrepreneurship is difficult. Studies have investigated the practical implications of neuroscience in the field of management and entrepreneurship through coupling and co-citation analyses (Cucino et al, 2021), but these researchers have not clearly described the respective differences. In this study, we observed that neuroscience and entrepreneurship have a clear relationship; thus, discussing the common methodologies and trends underlying neuroentrepreneurship research is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…To answer this study’s research question in a solid and “new” way, we offer a first systematization of contributions on managerial decision making that implement neuroscience techniques/points of view; thus allowing this review to robustly inform the affect-cognition debate. In this regard, a series of position papers/reviews/commentaries have been published about the impact of neuroscience approach and techniques in management studies (e.g., Becker et al, 2011 ; Powell, 2011 ; Ashkanasy et al, 2014 ; Ward et al, 2015 ; Jack et al, 2019 ; Massaro et al, 2020 ; Cucino et al, 2021 ), but only a few looked at the decision-making processes of managers within organizations. The sole contribution that tried to look at the influence of neuroscience studies in managerial decision making was Butler et al (2016) ; however, for their results categorized under the “organizational behavior cluster” heading, some of the 12 contributions in that sample did not deal with managerial decision-making processes (e.g., Peterson et al, 2008 ), as well as it was not focused on shedding light on the affect-cognitive debate.…”
Section: Introductionmentioning
confidence: 99%
“…At the micro- level, VCC factors enable dyadic interactions between individual actors (Cucino et al. , 2022) to integrate resources so as to co-create value with other actors through the blockchain: VCC outcomes benefit individual actors (Beirão et al.…”
Section: Resultsmentioning
confidence: 99%